Macrophage Apoptosis and Efferocytosis in the Pathogenesis of Atherosclerosis - Linton, MacRae F. (Circ J, 2016)
Macrophage apoptosis and the ability of macrophages to clean up dead cells, a process called efferocytosis, are crucial determinants of atherosclerosis lesion progression and plaque stability. Environmental stressors initiate endoplasmic reticulum (ER) stress and activate the unfolded protein response (UPR). Unresolved ER stress with activation of the UPR initiates apoptosis. Macrophages are resistant to apoptotic stimuli, because of activity of the PI3K/Akt pathway. Macrophages express 3 Akt isoforms, Akt1, Akt2 and Akt3, which are products of distinct but homologous genes. Akt displays isoform-specific effects on atherogenesis, which vary with different vascular cell types. Loss of macrophage Akt2 promotes the anti-inflammatory M2 phenotype and reduces atherosclerosis. However, Akt isoforms are redundant with regard to apoptosis. c-Jun NH(2)-terminal kinase (JNK) is a pro-apoptotic effector of the UPR, and the JNK1 isoform opposes anti-apoptotic Akt signaling. Loss of JNK1 in hematopoietic cells protects macrophages from apoptosis and accelerates early atherosclerosis. IκB kinase α (IKKα, a member of the serine/threonine protein kinase family) plays an important role in mTORC2-mediated Akt signaling in macrophages, and IKKα deficiency reduces macrophage survival and suppresses early atherosclerosis. Efferocytosis involves the interaction of receptors, bridging molecules, and apoptotic cell ligands. Scavenger receptor class B type I is a critical mediator of macrophage efferocytosis via the Src/PI3K/Rac1 pathway in atherosclerosis. Agonists that resolve inflammation offer promising therapeutic potential to promote efferocytosis and prevent atherosclerotic clinical events.